Draft Five Year Plan 1978-83 General Areas Vol. IV Industries and Minerals, Transport and Communications Government of Assam - Planning Commission (Planning Commission, 1978)
The total outlay for the Fifth Plan period was 1400 Lakhs for implementation of various Schemes . The main outlays were-share participation and loan to Assam Industrial Development Corporation and various other public and private sector projects including Ashok Paper Mills, Caustic soda and Chlorine Plant and petro-Chemicals project, etc., share participation in Assam Gas Company and Assam Tea Corporation, development of Industrial areas and training of Personnel and preparation of feasibility reports. An amount of Rs. 784.739 lakhs has been spent during the four years of the period up-to 1977-78.
Government of Assam, Planning and Development Department
Government of Assam, Planning and Development Department